Non-coding roX RNAs Prevent the Binding of the MSL-complex to Heterochromatic Regions. - Figueiredo, M.L.; Kim, M.; Philip, P.; Allgardsson, A.; Stenberg, P.; Larsson, J. (PLoS Genetics, 2014)
Long non-coding RNAs contribute to dosage compensation in both mammals and Drosophila by inducing changes in the chromatin structure of the X-chromosome. In Drosophila melanogaster, roX1 and roX2 are long non-coding RNAs that together with proteins form the male-specific lethal (MSL) complex, which coats the entire male X-chromosome and mediates dosage compensation by increasing its transcriptional output. Studies on polytene chromosomes have demonstrated that when both roX1 and roX2 are absent, the MSL-complex becomes less abundant on the male X-chromosome and is relocated to the chromocenter and the 4th chromosome. Here we address the role of roX RNAs in MSL-complex targeting and the evolution of dosage compensation in Drosophila. We performed ChIP-seq experiments which showed that MSL-complex recruitment to high affinity sites (HAS) on the X-chromosome is independent of roX and that the HAS sequence motif is conserved in D. simulans. Additionally, a complete and enzymatically active MSL-complex is recruited to six specific genes on the 4th chromosome. Interestingly, our sequence analysis showed that in the absence of roX RNAs, the MSL-complex has an affinity for regions enriched in Hoppel transposable elements and repeats in general. We hypothesize that roX mutants reveal the ancient targeting of the MSL-complex and propose that the role of roX RNAs is to prevent the binding of the MSL-complex to heterochromatin.